The ASAS-SN catalogue of variable stars – VIII. 'Dipper' stars in the Lupus star-forming region. Issue 3 (10th June 2020) - Bredall, J W; Shappee, B J; Gaidos, E; Jayasinghe, T; Vallely, P; Stanek, K Z; Kochanek, C S; Gagné, J; Hart, K; Holoien, T W-S; Prieto, J L; Van Saders, J
ABSTRACT: Some young stellar objects such as T Tauri-like 'dipper' stars vary due to transient partial occultation by circumstellar dust, and observations of this phenomenon inform us of conditions in the planet-forming zones close to these stars. Although many dipper stars have been identified with space missions such as Kepler / K2, ground-based telescopes offer longer term and multiwavelength perspectives. We identified 11 dipper stars in the Lupus star-forming region in data from the All-Sky Automated Survey for SuperNovae (ASAS-SN), and further characterized these using observations by the Las Cumbres Global Observatory Telescope (LCOGT) and the Transiting Exoplanet Survey Satellite ( TESS ), as well as archival data from other missions. Dipper stars were identified from a catalogue of nearby young stars and selected based on the statistical significance, asymmetry, and quasi-periodicity or aperiodicity of variability in their ASAS-SN light curves. All 11 stars lie above or redwards of the zero-age main sequence and have infrared (IR) excesses indicating the presence of full circumstellar discs. We obtain reddening–extinction relations for the variability of seven stars using our combined ASAS-SN- TESS and LCOGT photometry. In all cases, the slopes are below the ISM value, suggesting larger grains, and we find a tentative relation between the slope (grain size) and the $K_\text{s}-[22 \, \mu \text{m}]$ IR colour regarded as a proxy for disc evolutionary state.